Sex differences in fatigue resistance are muscle group dependent - Avin, K. G.; Naughton, M. R.; Ford, B. W.; Moore, H. E.; Monitto-Webber, M. N.; Stark, A. M.; Gentile, A. J.; Frey, L.; Laura, A. (Medicine & Science in Sports & Exercise, 2010)
Purpose: Women are often reported to be generally more resistant to fatigue than men for relative-intensity tasks. This has been observed repeatedly for elbow flexors, whereas at the ankle, sex differences appear less robust, suggesting localized rather than systemic influences. Thus, the purpose of this study was to examine sex differences in fatigue resistance at muscle groups in a single cohort and which factors, if any, predict endurance time.